O impulso utópico em The Wanting Seed - Silva, Débora Heloisa da (Universidade Federal de São Carlos, 2014)
This dissertation seeks to analyze the dystopic novel The Wanting Seed (1962), by the English writer Anthony Burgess with the objective of identifying in which way both structure and the development of the work points to, at an aesthetic level, the global feeling of utopia, which Fredric Jameson (2007) calls utopic desire or utopic impulse, which is present in daily life, in politics, in social movements and revolutions. Through the political reading, this research tries to show that, far beyond a novel about a degenerated future by overpopulation, this book presents, in its formal contradictions, much from the social, political and economic global movement of which it is part.
Keywords: Literatura; Impulso utópico; Crítica dialética; Burgess, Anthony, 1917-1993; Utopic impulse; Dialectic criticism; Anthony Burgess; LINGUISTICA, LETRAS E ARTES::LETRAS